Effects of Methanol Extract of Albizia lebbeck Leaves on the Body Weight, Hematological Parameters and Histological Structures of Digestive Organs in Rats (Rattus norvegicus) - Aroni, Gwakisa; Assey, Remmy; Mwangengwa, Lusekelo (Journal of Biology and Life Science, 2024)
Due to its use in traditional medication and its leaves and pods being considered as potential fodder for livestock the toxicity of Albizia lebbeck needs to be thoroughly explored. The study evaluated the effects of 70% methanol extract of Albizia lebbeck leaves on body weight, hematological parameters and histopathology of digestive organs in Wistar rats. Twenty-one healthy adult female rats were experimented with and divided into two groups of six and fifteen animals. Six rats were randomly subdivided into two groups of three rats each for plant extract LD50 determination at 2000 mg/kg and 5000 mg/kg dosages, respectively. Fifteen rats were randomly sub-allotted into three groups of five animals. Group I the control received distilled water by gavaging. Groups II and III received 100mg/kg and 400mg/kg of the extract, respectively—treatment covered 30 days. On day 31, the body weight of each rat was recorded before being sacrificed under chloroform. Blood was collected for hematological analysis. The liver and stomach were trimmed and processed for histopathology. The results revealed the LD50 of the extract to begreater than 5000 mg/kg. Extract treatment had no significant effects on the rat’s body weight. A significant (P<0.05) increase in WBC, Eosinophils, RBC, and Hematocrit was revealed at 100 mg/kg of extract treatment. A dosage of 400 mg/kg of the extract caused a significant increase in Eosinophils and Lymphocytes. However, the plant extract caused a significant (P<0.05) decrease in Mean Platelet Volume and Platelet Distribution Width at both doses, Monocytes and Neutrophils at 400 mg/kg and Mean Corpuscular Volume and Mean Corpuscular Hemoglobin at 100 mg/kg compared with the control. Both doses of the extract treatments caused lesions in the liver characterized by, necrosis, sinusoidal dilatation and inflammatory cell infiltration with no significant lesions in the stomach. In conclusion, the extract of Albizia lebbeck leaves caused a significant decrease in some hematological parameters and some lesions in the liver at 100 mg/kg and 400 mg/kg.